The role of WhatsApp in sustaining emotional intimacy in long distance romantic relationships - Tshoagong, Gomolemo (The IIE, 2020)
In this study, the researcher set out to explore the role of WhatsApp in sustaining emotional intimacy in long-distance romantic relationships. The aim was to find out how this can be achieved through the utilisation of the various features of WhatsApp. Using a qualitative design, a study was conducted using semi-structured interviews with males and females between the ages of 25-35 who are based in Johannesburg, Midrand, and are currently involved in long-distance romantic relationships. This was o gain understanding about their experiences with utilising WhatsApp as a platform of communication in their relationships, and to get subjective accounts of how this assists with sustaining emotional intimacy. The most findings indicated that couples were able to sustain emotional intimacy through the use of WhatsApp. The least findings were related to bad relationship quality, with most participants stating a general satisfaction. The overall findings indicated that the respondents found WhatsApp to be an effective channel of communication in their long-distance relationships.
Keywords: WhatsApp; Long-distance relationships; Emotional intimacy; Voice messaging; Video calling; Text messaging